Metbod Development of Allele Specific PCR Assay for CYP2B6 - Mohd Iqbal, Zulkafli (Universiti Sains Malaysia, 2009)
CYP2B6 is one of the drug-metabolizing enzymes that catalyses many types of clinical drugs such as anti-cancer drugs, anti-malarial drugs and anti depressant drugs. Among other types of CYP isoforms, CYP2B6 is poorly characterized. It was initially thought that CYP2B6 constitute only small portion of total hepatic CYP (Shimada et al., 1994) and expressed in low level (Mimura eta/., 1993 and Yamano et al., 1989). Since most of the substrates of CYP2B6 are clinically important drugs, determination of CYP2B6 polymorphism in the population is important. We successfully developed a simple and specific method of Allele-Specific Multiplex Polymerase Chain Reaction (PCR) for the detection of CYP2B6 single nucleotide polymorphisms (SNP). DNA was extracted from blood and was subjected to a first PCR which amplify a portion of exon I, exon 3 and 4 region of the gene. After that second PCR was used to detect polymorphism sites ofCYP2B6 using primers that were allele specific. Sequencing was performed to validate the test results. As for conclusion we successfully developed simple and specific method for the detection of 62 A>T, 76 A>T and 157618 C>T polymorphism in CYP2B6 gene. Allele-specific PCR is proved to be specific with the ability to apply the nested technology where our method managed to separate CYP2B6 from the similar CYP2B7. We also managed to optimize multiplex reaction of two primers and the result was satisfying.